An Empirical Test Of Financial Ratios For Malaysian Practice Notes No.4 (PN 4) Sector Companies. - Ali, Ruhani; Woon, Jeng Hoong (2003)
Corporate failures are known to have high economic cost due to its impact on to investors, creditors, auditors, market analysts, loan officer, and also to the management and employees of the affected companies. Due to this reason, a fast and efficient device or model is needed to detect financially distressed companies.